ENHANCING SPEAKING SKILLS THROUGH TASK-BASED LEARNING IN ELT CLASSROOMS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
In the context of English Language Teaching (ELT), speaking skills are often identified as crucial but challenging to develop. Task-Based Learning (TBL) has emerged as an effective pedagogical approach to enhance speaking proficiency, emphasizing communication through real-world tasks